Analisis Kreativitas Siswa dalam Pemecahan Masalah Matematis Pada Materi Pecahan di Kelas IV SD Negeri Kadilangu 1 - Lovika Ardana Riswari; Sayyidatul Munnah; Syafira Ashna Putri Nuha (Jurnal Lensa Pendas, 2023)
Student creativity can be seen from the way students solve fraction problems. The purpose of this research is to analyze students' creativity in solving math problems in fraction material at SD Negeri Kadilangu 1. This type of research is descriptive qualitative. The subjects of this study were fourth grade students at Kadilangu 1 Public Elementary School. The data collection techniques in this study were mathematical ability tests, mathematical solving tests, and interviews. Data analysis techniques using data reduction, data presentation, and drawing conclusions. The data validation technique uses triangulation by analyzing test results and interviews. Based on this research, it was found that the mathematical problem-solving skills of IV students at Kadilangu 1 Public Elementary School in understanding the problem, preparing a problem-solving plan, designing a problem-solving plan, and re-examining all the steps that had been carried out were classified as moderate. Because each student has their own way of solving mathematical problem solving.